IVAN FRANKO AND “HODACHKOVA” GENTRY OF BEREZIV - Genyk, L. Ya. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article once again returns to the origin of world-renowned researchers Ukrainian writer and poet, historian and economist, politician and literary critic Ivan Franko of petty noblemen and exposes its links with the same nobility from the village of Bereziv Nyzhhiy, Colomya County, Galicia (today – Kosiv district, Ivano-Frankivs’k region, Ukraine). The article reveals the writer’s influence on the organization of the Radical Party in the village of Bereziv and educational activities of people from this village in the Diaspora: Cyril Genyk-Berezovskyi (1857-1925), Basil-Yaroslav Arsenych-Berezovskyi (1887-1953), Julian (Yulian) Genyk-Berezovskyi (1906-1952), Constantyn Genyk-Berezovskyi (1919-1988), John (Ivan) Kuzych-Berezovskyi (1903-1985), gentry emblem Sas and many others.